Associations of Gut and Circulating Microbiota with Circulating Vitamin D3, Type I Interferon, and Systemic Inflammation in Chronic Spontaneous Urticaria Patients - Yang Z; Song Y; Chen B; Hao F (Dove Medical Press, 2024)
Zhi Yang,1 Yao Song,1 Bangtao Chen,2 Fei Hao1 1Department of Dermatology, Third Affiliated Hospital of Chongqing Medical University, Chongqing, 401120, People's Republic of China; 2Department of Dermatology, Chongqing University Three Gorges Hospital, School of Medicine, Chongqing University, Chongqing, 404100, People's Republic of ChinaCorrespondence: Bangtao Chen; Fei Hao, Email medisci@163.com; haofei62@163.comObjective: To analyze the associations of the gut and circulating microbiota with circulating vitamin D3 (VD3), type I interferon (IFNI), systemic inflammation, and clinical profiles in chronic spontaneous urticaria (CSU) patients.Methods: A total of 36 CSU patients with VD3 insufficiency (VDI; serum 25(OH)VD3 < 30 ng/mL) and 36 sex-, age-, and body mass index-matched CSU patients with non-VDI were enrolled. Fecal and serum bacteria were identified through 16S rRNA sequencing, and serum 25(OH)VD3 and inflammation biomarkers were assessed using ELISA kits. IFNI response was determined by measuring the stimulatory activity of serum on IFNI-stimulated response element in HEK293 cells in vitro with luciferase assays.Results: Higher urticarial activity score over 7 days (UAS7), higher frequency of levocetirizine resistance, and more severe proinflammation but weaker IFNI response were observed in VDI than non-VDI patients (all P< 0.05). IFNI response was strongly positively associated with serum 25(OH)VD3 level in both groups (P< 0.001). Compared to non-VDI patients, abundance of the fecal genera Prevotella 9, Escherichia-Shigella, and Klebsiella was significantly increased, while Bacteroides, Faecalibacterium, and Agathobacter were remarkably reduced in VDI patients (all P< 0.05). Burkholderia-Caballeronia-Paraburkholderia (40.95%), Acinetobacter (3.05%), and Aquabacterium (2.37%) were the top three bacteria in sera from VDI patients. Both serum 25(OH)VD3 level and IFNI response were positively associated with fecal Bacteroides in the two groups (P< 0.05). In non-VDI patients, there were moderately positive associations between IFNI response and fecal Lachnoclostridium, unclassified_f__Lachnospiraceae, and Phascolarctobacterium and between serum 25(OH)VD3 level and fecal Lachnoclostridium (all P< 0.01). Circulating microbiota in VDI patients was closely related only to proinflammation and UAS7 (both P< 0.05).Conclusion: Changes in gut but not circulating microbiota composition are associated with serum 25(OH)VD3 insufficiency and impaired IFNI homeostasis, which points to greater disease severity (UAS7) and systemic proinflammation in CSU patients.Keywords: chronic spontaneous urticaria, microbiota, vitamin D3, type I interferon, inflammation